Improving Dribbling Skills Through a Combination of Ladder Drills and Ball Feeling Exercises for Futsal Athletes - Dikri Farhanul Qolbi; Alen Rismayadi; Moch Yamin Saputra (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
The purpose of this study was to analyze the extent to which dribbling skills can be improved through a combination of ladder drill and ball feeling exercises in futsal players. This study used an experimental method with a one-group pretest posttest control design. The population of DNA FC Bandung futsal athletes was 14 and the sampling technique used total sampling. The results of the independent t-test had a t-value of -4.524 with a Sig. (2-tailed) value of .001. Because the Sig. (2-tailed) value <0.05, Ho was rejected. It was concluded that the combination of ladder drill and ball feeling exercises had a significant effect on improving dribbling skills in futsal athletes. It is recommended for futsal coaches and athletes to interpret the combination of these exercises into a routine training program, it is hoped that players' dribbling skills can be further developed so that players can be more proficient and confident on the field.